PREDICTIVE FACTORS FOR PEDIATRIC INTENSIVE CARE UNIT (PICU) ADMISSION IN CHILDREN WITH ASTHMA EXACERBATION IN MCH, ALAHSA - Dr. Jaber Abdullah Al Habeeb; Dr. Zainab Sami M. Aljizeeri (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background and objective: Childhood asthma is recognized to be one of the most common chronic diseases in children. Several national and international reports have demonstrated an increase in the prevalence of pediatric asthma and asthma-related Pediatric Intensive Care Unit (PICU) admissions. In addition, PICU admission among asthmatic children has been associated with an increase in the risk of asthma-related mortality. However, the predictors and risk factors of acute severe asthma that required PICU admission haven’t been identified. Thus, the purpose of this study was to investigate the predictive factors for PICU admission in children with asthma exacerbation. Methodology: This study was conducted at the inpatient pediatric department of Maternity and Children Hospital (MCH), Alahsa, Saudi Arabia. Seventy-eight asthmatic patients, aged 1-13 years, who were admitted to either PICU or general pediatric ward as a case of asthma exacerbation between October 2022 and May 2023, were enrolled in this study. The diagnosis of asthma was identified by a pediatric allergist or pulmonologist who were involved in the inpatient or outpatient management care. The study design was a cross-sectional. The data collection sheet consisted of 6 sections of different variables including demographical data, characteristics of the current acute asthma exacerbation, asthma history, classification of asthma severity, asthma controlling therapy, and environmental triggers and atopy. The data was collected from the patients’ medical records and by interviewing the patients’ parents/caregivers. Results: A total of 78 patients were enrolled in the study over a period of 8 months. Fifty-seven patients (73.1%) were admitted to the pediatric ward and 21 patients (26.9%) were admitted to the PICU. The gender ratio was approximately equal, with slight male predominance (56.4%). The mean age for the overall study population was 4.0 ± 2.6 years. The majority of the patients have healthy weight (42.3%) in both groups, with no obese patient was admitted to the PICU. Baseline mean SPO2 saturation was found to be higher in those admitted to the ward (p=.000). Around 87% of the patients received systemic steroids at the ED before hospitalization. The percentage of patients who used systemic steroids in the ED was higher for those admitted to the PICU. Around 97% of the patients’ exacerbations were triggered by infection. Meanwhile, mean length of stay was found to be approximately 33% (4.4 ± 2.2) higher in the PICU admissions (p=.043). Less than one-fifth of the total cohort has been found to be following up in the outpatient clinic the previous year (11/78, 14%). The history of prior therapy with ICS was found to be more prevalent in those who were admitted to PICU. Similarly, previous PICU admissions and prior hospital admissions were also more prevalent in those admitted to the PICU. However, it hasn’t been shown to be statically significant. Statistically significant differences were detected between SpO2 levels among children who were admitted to PICU as compared to those admitted to the pediatric ward, (86.2 ± 6.8%, p=.000). For each unit increase in the SpO2, there is a 0.8-fold increase in the odds of being admitted to the PICU (OR 0.8, 95% CI: 0.7–0.8, p=0.001). Nevertheless, pCO2 was another predictive factor for PICU admission, (OR 1.1, 95% CI: 1.0–1.2, p=0.013). Notably, previous PICU admission, last year admissions, and last year ED visits could not be quantified as predictive factors for PICU admission with statistical significance. Similarly, risk analysis between PICU admission and the type and severity of asthma did not reveal statistically significant results. Conclusion: Oxygen saturation (SpO2) measurements at the ED and pCO2 level are predictors of needing intensive care admission for children with acute severe asthma exacerbation, aged 1–13 years. Further large-scale studies are needed to explore the modifiable predictors that would help in identifying children with a high risk for intensive care admissions.